2000
DOI: 10.1029/2000wr900159
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic study of nonlinear solute transport in a groundwater–surface water system Under steady state and transient hydraulic conditions

Abstract: Abstract. Two laboratory experiments were conducted to investigate the effects of tides and buoyancy on beach hydraulics in the presence of a seaward groundwater flow due to an elevated "regional" water table. In the first experiment, case 1, the difference in concentration between the salt water at sea and the water of the regional aquifer was small, 2.4 g L -•, such that it did not engender density gradients; the salt acts as a tracer in this case. In the second experiment, case 2, the difference was --•32.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(156 citation statements)
references
References 29 publications
12
143
1
Order By: Relevance
“…Where the USP is present, FSGD travels below the USP and discharges near the low tide mark in a zone bounded by the USP and the saltwater wedge. Numerous field, numerical and 14 laboratory studies have observed this salinity distribution in tidally-influenced CUAs [e.g., Lebbe, 1981;Boufadel, 2000;Mango et al, 2004;Vandenbohede and Lebbe, 2005;Boufadel et al, 2006;Mao et al, 2006;Robinson et al, 2006;Robinson et al, 2007b;Yang et al, 2013;Buquet et al, 2016]. The USP, in comparison with the DZ of the saltwater wedge, is a more active zone of saltwater-freshwater mixing in a CUA and an important feature of the STE system [Robinson et al, 2007b;Thorn and Urish, 2013].…”
Section: Tidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Where the USP is present, FSGD travels below the USP and discharges near the low tide mark in a zone bounded by the USP and the saltwater wedge. Numerous field, numerical and 14 laboratory studies have observed this salinity distribution in tidally-influenced CUAs [e.g., Lebbe, 1981;Boufadel, 2000;Mango et al, 2004;Vandenbohede and Lebbe, 2005;Boufadel et al, 2006;Mao et al, 2006;Robinson et al, 2006;Robinson et al, 2007b;Yang et al, 2013;Buquet et al, 2016]. The USP, in comparison with the DZ of the saltwater wedge, is a more active zone of saltwater-freshwater mixing in a CUA and an important feature of the STE system [Robinson et al, 2007b;Thorn and Urish, 2013].…”
Section: Tidesmentioning
confidence: 99%
“…This time-averaged circulating flow can lead to the formation of an upper saline plume (USP, Figure 1) [Robinson et al, 1998;Boufadel, 2000;Mango et al, 2004;Vandenbohede and Lebbe, 2005;Robinson et al, 2007b]. Where the USP is present, FSGD travels below the USP and discharges near the low tide mark in a zone bounded by the USP and the saltwater wedge.…”
Section: Tidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have investigated periodic unsaturated groundwater flow via numerical solution of Richards' equation (e.g. Boufadel et al, 1998;AtaieAshtiani et al, 1999;Boufadel, 2000;Naba et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The solute mass conservation equation is written in terms of mass fraction as follows (Boufadel, 2000;Cardenas et al, 2007;Younes et al, 2009;Zidane et al, 2012):…”
Section: Mathematical Modelmentioning
confidence: 99%